Caracterização micrometeorológica e estimativa do balanço hídrico em bacias com formação de campos naturais e floresta no interflúvio entre os rio Purus e Madeira - Tartari, Rodrigo (2017)
This work aimed to investigate the seasonality of micrometeorological components using automatic stations installed in regions where forest formations and natural fields occur in the middle course of the Madeira River. The real evapotranspiration component was determined by Penman Montheit to evaluate the water balance at the watershad level for year 2013, associated with geoprocessing, flow monitoring and rainfall-flow simulation techniques. During the period from December to February, the highest irradiance at the top of the atmosphere (Ro) was detected and in June and July the lowest maximum. During the rainy season, the presence of clouds is intense and of high density, it inhibits the passage of the radiation, occurring in August the highest value of global radiation (Rg) in the forest, in comparison to the fields that showed its maximum value in the month of September. The average annual radiation ratio at the top of the atmosphere (Rg/Ro) was 46.5% in the forest area and 44.5% in the field area. The balance of radiation in the forest corresponds to 73% of the global radiation (Rn/Rg), while in the fields this percentage was 61%. The soil heat flux in the forest area corresponds to less than 2% of the radiation balance (G/Rn) and in the fields to 22%. The forest behaves like a barrier of airflow movements, preventing the exchange of heat with the atmosphere. They observed five days with the occurrence of abrupt reduction of air temperature due to the effect of the cold caused by mass of polar origin that did not reach the height of 5m in the forest. The relative air humidity (HR) was superior in the forest in relation to the fields and with instantaneous minima below 30% in August. The winds are predominant coming from the North quadrant and less frequently from the south direction with occurrence in July. In the transition from the rainy period to the dry season, there are occurrences of winds coming from the West and in the dry months there is occurrence of easterly winds. The average velocity of the winds is higher in the field areas in approximately 2 m.s-1 the forest region in all months, with greater amplitude in the transition months from rainy to dry and in the dry period. Evapotranspiration was higher in the forest with a mean of 3.9±1 mm.day-1 in relation to the fields that presented 2.9±1 mm.dia-1 . The percentage of evapotranspiration that returns to the atmosphere of the forest area corresponds to 66.6% of the total annual precipitation of 2197.5 mm, and in the field area to 49.5%. The flow in the basin forest-fields, in the dry season, remained minimal draining to the water, different from the forest stream that registered zero flow characterizing intermittence. The daily flows were simulated using the IPH2 model adjusted to the monitoring events, with results that correspond to the effects of seasonality and rainy events. The monthly water balance shows that the volume of water in the soil decreases first in the field area because direct radiation propagates on the surface more intensely at the time. In the rainforest even during the rainy season, the volumes of water in the soil are slightly smaller than the fields, related to the higher evapotranspiration occurring. However, the forest has the capacity to store water for a longer period, when the rainfall decreases, and in June and July the water deficiencies are equalized, and in September when the fields begin to accumulate water more quickly due to the direct entrance of the precipitation, where the interception does not occur. During the transition from the dry period to the rainy season, there are signs of increasing both the availability of water in the soil and also the increase in flow, and that is when the forest stream returns to the water.